2014
DOI: 10.1177/1548051814529825
|View full text |Cite
|
Sign up to set email alerts
|

More Alike Than Different

Abstract: The purpose of this study was to extend generations research by investigating similarities and differences regarding the importance generations place on the presence of various workplace characteristics. We hypothesized (1) that similarities in the importance of workplace factors between generations would be more prevalent than differences and (2) that the importance of the workplace factors would have consistently similar or different moderating effects among generations on the relationships between employee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 51 publications
2
23
0
2
Order By: Relevance
“…Learning-and-development leaders need to realize that all employees within a generational cohort do not necessarily value the same things (Mencl & Lester, 2014;Wong et al 2008).…”
Section: Generational Similaritiesmentioning
confidence: 99%
“…Learning-and-development leaders need to realize that all employees within a generational cohort do not necessarily value the same things (Mencl & Lester, 2014;Wong et al 2008).…”
Section: Generational Similaritiesmentioning
confidence: 99%
“…However, these characterizations of great places to work are confounded by a myriad other somewhat idiosyncratic suggestions at the individual, leadership, work group, and organizational levels. At the individual level, factors such as good physical workspace and compensation, recognition, caring human resource, learning and career development opportunities, flexibility, job satisfaction, challenging work, etc., have been suggested to characterize great places to work (Park et al, 2015;Mencl & Lester, 2014;Butler, 2014).…”
Section: Great Places To Work: An Overviewmentioning
confidence: 99%
“…At the leadership level, it is suggested that great places to work have inspiring, authentic, and servant leadership (Henderson, 2011;Love & Singh, 2011;McGee-Cooper & Trammell, 2010). At the group level, factors such as team spirit, mutuality, cohesiveness, group focused processes, quality relationship, authentic behavior, collaboration, diversity are stated to signal great places to work (Park et al, 2015;Mencl & Lester, 2014;Crainer, 2014;Taskinen, 2011). Finally, at the organizational level, studies suggest that factors such as low levels of hierarchy, consistent assessment practices, autonomy, focus on employee wellness and engagement, worklife balance, safety orientation, fun work environment, transparency, accountability, civility and networking opportunities, focus on all stakeholders, corporate citizenship behavior, community oriented policies, social goals, and well laid out and easily accessible ethics statement are indicative of great places to work (Hoover & Pepper, 2014;Philipsen, 2014;Hinkin & Tracey, 2010;Bakker, 2010;Bernardi, Bosco & Vassill, 2006;DeCotiis, Sullivan, Hyatt, & Avery, 2004;van Marrewijk, 2004;Joyce, 2003).…”
Section: Great Places To Work: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hillebrandt and Ivens (2013) Found work life balance (WLB) as one of the factors affecting employer brand of the organization. Mencl and Lester (2014) In their studies differences emerged regarding career advancement opportunities, diversity climate, and immediate recognition and feedback, which were more valued by Generation Y.…”
Section: Berthon Et Al (2005)mentioning
confidence: 99%